2016
DOI: 10.3847/0004-637x/829/1/6
|View full text |Cite
|
Sign up to set email alerts
|

ALMA OBSERVATIONS OF HD 141569’s CIRCUMSTELLAR DISK

Abstract: We present ALMA band 7 (345 GHz) continuum and 12 CO(J = 3-2) observations of the circumstellar disk surrounding HD141569. At an age of about 5 Myr, the disk has a complex morphology that may be best interpreted as a nascent debris system with gas. Our 870 µm ALMA continuum observations resolve a dust disk out to approximately 56 au from the star (assuming a distance of 116 pc) with 0."38 resolution and 0.07 mJy beam −1 sensitivity. We measure a continuum flux density for this inner material of 3.8 ± 0.4 mJy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(94 citation statements)
references
References 58 publications
9
84
1
Order By: Relevance
“…The companion to HD142527, which is located well within the gap in the disk, is commonly interpreted as having too low a mass (0.13 M e ; Lacour et al 2016) and eccentricity to generate the observed spiral arms, so this object is included in our sample (although see Price et al 2018). Lastly, we removed HD141569 from the sample, because its low dust mass (on the order of 1 M ⊕ or less; Flaherty et al 2016;White et al 2016) makes the system prone to radiation pressure and photoelectric instability, which can also produce spiral arm structures (e.g., Richert et al 2018b). …”
Section: Disk Imaging Samplementioning
confidence: 99%
“…The companion to HD142527, which is located well within the gap in the disk, is commonly interpreted as having too low a mass (0.13 M e ; Lacour et al 2016) and eccentricity to generate the observed spiral arms, so this object is included in our sample (although see Price et al 2018). Lastly, we removed HD141569 from the sample, because its low dust mass (on the order of 1 M ⊕ or less; Flaherty et al 2016;White et al 2016) makes the system prone to radiation pressure and photoelectric instability, which can also produce spiral arm structures (e.g., Richert et al 2018b). …”
Section: Disk Imaging Samplementioning
confidence: 99%
“…Millimeterwavelength interferometry provided the first spatially resolved observations of the molecular gas emission in a debris disk (Hughes et al 2008a), and the improved sensitivity and angular resolution of the Atacama Large Millimeter/submillimeter Array (ALMA) has led to a resurgence of interest in these objects, resulting in spectacular gas and dust imaging of the recently discovered HD 21997 disk Moór et al 2013), the iconic β Pictoris disk (Dent et al 2014), and recently the first gas-bearing debris disk around a solar-type star (HD 181327; Marino et al 2016). Another object of interest has been the optically thin dust disk around the 5 Myr old Herbig Ae star HD 141569, whose classification as a transitional or debris disk has been an object of intense discussion in the literature: recent observations with the Submillimeter Array (SMA) and Combined Array for Research in Millimeter-wave Astronomy (CARMA) have spatially resolved the gas disk for the first time (Flaherty et al 2016), and ALMA observations probe the disk in greater detail (White et al 2016). A survey for gas emission in a sample of 24 debris disks in the 10 Myr old Sco-Cen star-forming region has revealed that gas-rich debris disks are common around intermediate-mass stars, with gas detected around three of the seven A/B stars in the sample, but rare around FGK stars (Lieman-Sifry et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[O I] and [C II] emissions were also detected for β Pictoris (Brandeker et al 2016). Some debris disks are known to have submillimeter-wave CO emission; e.g., 49 Ceti (Dent et al 2005;Hughes et al 2008), β Pictoris (Fernández et al 2006;Dent et al 2014), HD 21997 (Moór et al 2011Kóspál et al 2013), HD 131835 (Moór et al 2015), and HD 141569 (White et al 2016).…”
mentioning
confidence: 99%